Biosensors nanotechnology - Tiwari, Ashutosh, 1978-; Turner, Anthony P. F. (Wiley ; Scrivener Publishing, 2014)
"This book provides detailed review chapters on a range of nanostructures such as nanoparticles, nanowires, nanotubes, nanoribbons, nanorods, nanobelts and nanosheets in the construction of biosensors with set applications of biosensors nanotechnology for biological and chemical analyses, food safety industry, biomedical diagnostics, clinical detection, and environmental monitoring. The authors provide a comprehensive view of cutting-edge research on advanced materials for healthcare technology and applications. The book is written for scientists, researchers, and clinicians from diverse backgrounds across chemistry, physics, materials science and engineering, medical science, pharmacy, biotechnology, and biomedical engineering"--Resumé vydavatele
Keywords: biosenzory; nanomateriály; nanosenzory; nanotechnologie; biosensors; nanostructure materials; nanosensors; nanotechnology; kolektivní monografie; elektronické knihy; collective monographs; electronic books